How do emotional exhaustion and work overload experienced by frontline employees influence perceived customer discrimination among minority customers? Mediating role of psychological contract violation - Aslam, Muhammad Shakeel; Ahmed, Farhan; Haq, Saif ul; Tariq, Samia (Pakistan Business Review, 2025)
COVID-19 has altered service operations and heightened job stressors for frontline employees in the service sector. The current study develops a conceptual model connecting pandemic-related job demands—emotional exhaustion and work overload—to perceived customer discrimination through psychological contract violation. More precisely, we propose that these job demands affect perceived customer discrimination directly and indirectly through psychological contract violation. We evaluated the hypotheses using matched employee–customer (dyadic) responses. A total of 299 usable dyadic responses were collected using self-administered questionnaires. Partial least squares structural equation model (PLS-SEM) supports hypothesized relationships. Both emotional exhaustion and work overload were positively associated with perceived overt and subtle discrimination. Moreover, psychological contract violation partially mediated these effects except for emotional exhaustion on overt discrimination. Finally, the paper discusses the implications of these findings for the service industry, along with limitations and future research directions.
Keywords: Job demands; emotional exhaustion; work overload; psychological contract violation; perceived customer discrimination; overt discrimination; subtle discrimination; employee–customer (dyadic) responses; service management